Dissecting the GA regulation of cell expansion in the root Arabidopsis thaliana - Cancho Sánchez, Ester (2013)
Gibberellins (GAs) represent an important class of hormonal signal that regulate growth and developmental processes during the plant life cycle. GA promotes growth through the targeted degradation of the nuclear localized DELLA repressor proteins via the ubiquitin proteasome pathway. Whilst DELLAs do not appear to bind directly to DNA, recent evidence suggests that they interact with several different classes of transcription factors to control the expression of downstream genes in a GA-dependent manner.